Research and publication trends on knee osteoarthritis and cellular senescence: a bibliometric analysis - Wang, Shuai; Yang, Jiyong; Xiang, Ruian; Li, Congcong; Li, Junyi; Shen, Xingxing; Liu, Wengang; Xu, Xuemeng (Frontiers in Physiology, 2023)
Background: Cellular senescence is associated with age-related pathological changes, senescent cells promote the development of knee osteoarthritis. A better understanding between knee osteoarthritis and cellular senescence may enhance the effectiveness of therapies that aim to slow or stop the progression of this disease.This study aimed to systematically analyze and visualize the publication trends, research frontiers and current research hotspots of knee osteoarthritis and cellular senescence by using bibliometrics.The publication search was performed on the Web of Science Core Collection database for documents published from 1992 to 2023. VOSviewer, Citespace, R package Bibliometrix and Microsoft Office Excel were used to study the characteristics of the publications. The publication number, countries, institutions, authors, journals, citations and co-citations, keywords were analyzed.Results: A total of 1074 publications were analyzed, with an average annual growth rate of 29.89%. USA accounted for the biggest contributor, ranked first in publications and citations. Publications of this field were published in 420 journals, OSTEOARTHRITIS and CARTILAGE was the most influential. A total of 5657 authors contributed to this research. The most productive author was Lotz, MK (n=31, H-index=22, Total citation=2619), followed by Loeser, R.F (n=16, H-index=14, Total citation=2825). However, the collaboration between authors was relatively weak. Out of the 1556 institutions involved, 60% were from the USA. Scripps Research ranked first with 25 papers and a total of 2538 citations. The hotspots of this field had focused on the pathomechanisms (e.g., expression, inflammation, apoptosis, autophagy, oxidative stress) and therapeutics (e.g., stem cell, platelet-rich plasma, transplantation, autologous chondrocytes, repair), and the exploration of Senolytics might be the important direction of future research. This is a provisional file, not the final typeset article Conclusion: Research on the cross field of knee osteoarthritis and cellular senescence is flourishing. Age-related pathomechanism maps of various cells in the joint and the targeted medicines for the senescent cells may be the future trends. This bibliometric study provides a comprehensive analysis of this cross field and new insights into future research.